Detection of Blast-Related Traumatic Brain Injury in U.S. Military Personnel - Mac Donald, Christine L; Johnson, Ann M; Cooper, Dana; Nelson, Elliot C; Werner, Nicole J; Shimony, Joshua S; Snyder, Abraham Z; Raichle, Marcus E; Witherow, John R; Fang, Raymond; Flaherty, Stephen F; Brody, David L (The New England journal of medicine, 2011)
In this study of injured U.S. military personnel, an advanced MRI technique found abnormalities consistent with traumatic axonal injury in some patients with mild traumatic brain injury after blasts; these abnormalities were not detected with conventional MRI. In the current wars in Iraq and Afghanistan, the number of blast-related traumatic brain injuries may be as high as 320,000. 1 Most of these injuries are categorized as uncomplicated “mild” or “concussive” traumatic brain injury on the basis of clinical criteria and the absence of intracranial abnormalities on computed tomography (CT) or conventional magnetic resonance imaging (MRI). 2 However, little is known about the nature of these “mild” injuries, and the relationship between traumatic brain injury and outcomes remains controversial. 3 , 4 No human autopsy studies conducted with the use of current immunohistochemical methods 5 , 6 have been published. 7 , 8 Computer simulations of . . .